Implications for Distance Learning: Does Demographics Impact Students’ Self-Perceived Proficiency in Information Technology? - Landor-Ngemi, Jarrett (Advances in Social Sciences Research Journal, 2022)
The purpose of this study is to investigate the impact of demographics on students’ self-perceived proficiency in information technology and its implication for distance learning. Data for this study were collected from students in both undergraduate and graduate programs. Even though research suggests that demographics have an impact on users of information technology, this study, however, reveals no statistically significant relationship exists between demographics and students’ self-perceived proficiency in information technology. The study however shows that most rated themselves as proficient in using spreadsheets, PowerPoint, conducting online research, using chat/thread discussions, and word processing while most students described themselves as below proficient in computer programming and Webpage design. This study also highlights the implications of the findings to distance learning.